2020
DOI: 10.1038/s41467-020-19131-y
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by environment interaction for gene expression in Drosophila melanogaster

Abstract: The genetics of phenotypic responses to changing environments remains elusive. Using whole-genome quantitative gene expression as a model, here we study how the genetic architecture of regulatory variation in gene expression changed in a population of fully sequenced inbred Drosophila melanogaster strains when flies developed in different environments (25 °C and 18 °C). We find a substantial fraction of the transcriptome exhibited genotype by environment interaction, implicating environmentally plastic genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…A genomics study in A. thaliana also revealed the major role of genotype-by-environment interactions in gene expression levels 36 . In addition, research on Drosophila melanogaster also found that a substantial fraction of the transcriptome exhibited genotype-by-environment interactions, suggesting an environmentally plastic genetic architecture of gene expression 37 . In this study, the G-type and NG-type leaves shared only a small percentage of DEGs under different light density conditions, which means that there are likely different regulatory mechanisms between G- and NG-type leaves under the different conditions that are affected by certain environment-specific promoters.…”
Section: Discussionmentioning
confidence: 99%
“…A genomics study in A. thaliana also revealed the major role of genotype-by-environment interactions in gene expression levels 36 . In addition, research on Drosophila melanogaster also found that a substantial fraction of the transcriptome exhibited genotype-by-environment interactions, suggesting an environmentally plastic genetic architecture of gene expression 37 . In this study, the G-type and NG-type leaves shared only a small percentage of DEGs under different light density conditions, which means that there are likely different regulatory mechanisms between G- and NG-type leaves under the different conditions that are affected by certain environment-specific promoters.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of four-seed pod as a vital factor affecting yield trait is jointly regulated by genotype and environment ( Liu et al, 2015 ). The influence of environment is potentially realized through the gene regulation network ( Huang et al, 2020 ). Therefore, exploring the pathways of genes involved is the key to understanding the formation of four-seed pod under different four-seed pod ratios, which implies the phenotypic effect of gene and environment ( Guo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For Indica and Japonica, 2,139 and 2,075 DPTs had significantly heritable plasticity, respectively (Supplementary Tables 22-23). Using these DPTs, we aimed to test for correlated expression patterns across genes, summarizing expression across co-expression modules and improving power to detect selection (Hämälä et al, 2019; Huang et al, 2020). Specifically, we examined whether some modules had stronger average selection on gene expression plasticity than others.…”
Section: Main Textmentioning
confidence: 99%
“…We used representative studies from the literature for determination of sample size (Des Marais et al, 2012; Gutteling et al, 2007; Huang et al, 2020; Lafuente et al, 2018; Ungerer et al, 2003; West et al, 2007). Individuals of each genetic identity were allocated randomly to the wet and dry environments and their planting order was randomized as laid out in an alpha lattice design.…”
Section: Main Textmentioning
confidence: 99%